EL FEDERALISMO ESPAÑOL EN LA HISTORIA: VOLVAMOS A PROUDHON (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This article presents an analysis of the philosophical bases of the integral federalism of P J Proudhon, as well in its historical process and its reception and its influence in Spain, by means of Pi y Margall, as in its real topicality in the current Spanish and European political debate. The author centers his study on the Proudhon’s cognitive theory or dialectical serial, key factor, in his opinion, not to fall in groundless conclusions, like that of alleged sound hegelianism, idealism abstracted, utopism, etc., so frequents unfortunately among the researchers who direct or indirectly have dealt with his thought.